Channel kultura radio CCP's video series on Philippine broadcasting as a cultural force - Tiongson, Angelito G.; Enriquez, Elizabeth L.; Casagan, Luzviminda (CCP, 2003)
A video documentary on the history Philippine radio broadcasting.